Realization of Terahertz Wavefront Manipulation Using Transmission-Type Dielectric Metasurfaces - Li, Jiaqi; Ning, Tingyin; Zhang, Min; Li, Ireng Ling; Su, Hong; Liang, Huawei (Frontiers in Physics, 2020)
Metasurfaces, composed of an array of subwavelength artificial structures, have attracted great interest, owing to their high ability in locally manipulating the wavefront of electromagnetic waves. Here, we propose a dielectric metasurface based on a fused silica resonator, consisting of a rectangular-shaped bar placed in the center of a cross net-shaped structure, to manipulate the wavefront of terahertz waves. As proof of concept, several transmission-type devices for spatial modulation are designed at the target frequency of 0.14 THz, including on-axis and off-axis focusing, generation of a non-diffracting Bessel beam, and multi-focus lens. The simulated efficiencies range from 45% to 62%. This novel approach for manipulating THz wavefronts can be also used for information storage and other phase-related techniques in the rapid development of THz applications.